Effects of Ozone Application on Microbiological Stability and Content of Sugars and Bioactive Compounds in the Fruit of the Saskatoon Berry (Amelanchier alnifolia Nutt.) - Józef Gorzelany; Ireneusz Kapusta; Miłosz Zardzewiały; Justyna Belcar (Molecules, 2022)
Saskatoon berry fruits are a valuable source of micro- and macronutrients, sugars, and compounds with health-promoting properties, the properties of which change during storage. This study presents the effects of applied gaseous ozone at 10 ppm for 15 and 30 min on microbiological stability, sugar content, and bioactive compounds for three cultivars and three clones of Saskatoon berry fruit. The ozonation process had a positive effect on reducing the microbial load of the fruit, which was observed on day 7 of storage for the two variants of ozonation time of 15 and 30 min compared to the control and also on the sugar profile of the “Thiessen” fruit, as well as clones no 5/6 and type H compared to the control sample, which was non-ozonated fruit. In the Saskatoon berry fruits analyzed, 21 polyphenolic compounds were identified, of which four belonged to the anthocyanin group whose main representative was the 3-O-glucoside cyanidin. The ascorbic acid content and antioxidant activity (determined by DPPH· and ABTS+· methods) varied according to the cultivar and clone of the Saskatoon berry fruits analyzed and the ozone exposure time.